Enhanced Power Density of Alcohol Biofuel Cell by Polymer‐assisted Crosslinks of 3D Graphene on Carbon Paper as the Bioanode. Issue 4 (27th August 2021) - Shi, Yuhe; Li, Lin; Zhang, Ling
Abstract: Herein, we successfully construct the 3D biocompatible graphene through crosslinking 2D graphene nanosheet onto carbon fiber paper with poly(diallyldimethylammonium chloride) (PDDA) as anode of the alcohol biofuel cell. Compared with the bioanode without 3D graphene, the current density and output power of PDDA‐graphene‐ADH bioanode is increased by 23 % and 41 % at a high concentration of ethanol at pH 8.9, suggesting the stabilization role of graphene in enzyme loading. The study provides us a deep analysis on structures and performances of the bioanode incl. electrochemistry, X‐ray photoelectron spectra, and atomic force microscopy images, which is significant to develop the new methods to construct 3D porous electrodes in energy conversion device. Abstract :